Transcriptome Assembly and Systematic Identification of Novel Cytochrome P450s in Taxus chinensis - Liao, Weifang; Zhao, Shengying; Zhang, Meng; Dong, Kaige; Chen, Ying; Fu, Chunhua; Yu, Longjiang (Frontiers in Plant Science, 2017)
Taxus spp. is a highly valuable medicinal plant with multiple pharmacological effects on various cancers. Cytochrome P450s (CYP450s) play important roles in the biosynthesis of active compounds in Taxus spp., such as the famous diterpenoid, Taxol. However, some specific CYP450 enzymes involved in the biosynthesis of Taxol remain unknown, and the systematic identification of CYP450s in Taxus has not been reported. In this study, 118 full-length and 175 partial CYP450 genes were identified in Taxus chinensis transcriptomes. The 118 full-length genes were divided into 8 clans and 29 families. The CYP71 clan included all A-type genes (52) belonging to 11 families. The other seven clans possessed 18 families containing 66 non-A-type genes. Two new gymnosperm-specific families were discovered, and were named CYP864 and CYP947 respectively. Protein sequence alignments revealed that all of the T. chinensis CYP450s hold distinct conserved domains. The expression patterns of all 118 CYP450 genes during the long-time subculture and MeJA elicitation were analyzed. Additionally, the expression levels of 15 novel CYP725 genes in different Taxus species were explored. Considering all the evidence, 6 CYP725s were identified to be candidates for Taxol biosynthesis. The cis-regulatory elements involved in the transcriptional regulation were also identified in the promoter regions of CYP725s. This study presents a comprehensive overview of the CYP450 gene family in T. chinensis and can provide important insights into the functional gene studies of Taxol biosynthesis.